Investigation of Maximum Power Point Tracking Methods in Photovoltaic Sytems - Karagözoğlu, Leyla; Duranay, Zeynep Bala (My University, 2023)
Leyla Karagözoğlu 1 , Zeynep Bala Duranay 2 Photovoltaic systems are one of the popular renewable energy sources as an alternative to fossil sources. Output power and efficiency of photovoltaic systems vary depending on changing environmental conditions. Finding the maximum power point during these changes has been an important problem. Because, operating the system at maximum power has a significant impact on overall system efficiency. Therefore, photovoltaic systems should be operated around the maximum power point to increase both power drawn and their efficiency. There are numerous methods for controlling the maximum power point. As input variables in these methods, factors such as open circuit voltage, short circuit current, radiation intensity, wind speed, and module temperature can be used. Furthermore, the complexity, cost, stability, convergence, and other characteristics of these maximum power point tracking methods vary. It has a variety of properties. As a result, determining the best maximum power point tracking method to use during the system's design phase is critical. Maximum power point tracking methods are classified into four categories in this study: traditional, smart, optimization, and hybrid. The benefits and drawbacks of these methods are determined, and their basic equations are provided. Keywords: Photovoltaic, Maximum Power, Maximum Power Point, Renewable Energy
Keywords: Renewable energy; Photovoltaic; maximum power; maximum power point